Gas Metal Rapid Arc Welding Potential - Hudec, Zdenek (Manufacturing Technology Journal, 2012)
The article presents problems with commercial inverter source Rapid Arc application on fillet and V-grooved welds. Principal and conditions of the process are explained and especially restriction due to source and feeder upper power limit is described. Case study of ``weld design for fabrication'' method was demonstrated, where type of weld and shape of groove is designed on the base of experimental results of process penetration behavior at 1/2 V-groove joint. Results are described and discussed, using special welding parameters monitoring equipment and software. A change of metal transfer behavior was recorded in accordance with torch angle setting and originally explained.
Keywords: GMAW; weld design for fabrication; Rapid Arc; stick-out; melting rate